Evaluation of the Possibility to Detect Circulating Tumor DNA From Pituitary Adenoma - Megnis, Kaspars; Peculis, Raitis; Rovite, Vita; Laksa, Pola; Niedra, Helvijs; Balcere, Inga; Caune, Olivija; Breiksa, Austra; Nazarovs, Jurijs; Stukens, Janis; Konrade, Ilze; Pirags, Valdis; et al. (Frontiers in Endocrinology, 2019)
Objective: Circulating free DNA (cfDNA) in general and circulating tumour DNA (ctDNA) in particular is becoming a more and more popular class of liquid biopsy biomarkers. In this study, we are investigating the ability to detect ctDNA from the plasma of pituitary adenoma (PA) patients. Design: Tumour tissue samples were obtained from planed PA resections, before which blood plasma samples were taken. Mutations found in PA tissue samples were evaluated in related cfDNA, isolated from plasma samples. Methods: Sanger sequencing, as well as previously obtained whole exome sequencing data, were used to evaluate mutation composition in tumour tissue samples. cfDNA was isolated from the same PA patients and competitive allele-specific TaqMan PCR and amplicon based next-generation sequencing (NGS) approach was used for targeted detection of mutations found in corresponding tumour tissue samples. Results: Using NGS-based analysis, we detected five out of 16 mutations in 40 % to 60 % of total reads, two mutations in 0.50 % to 5.00 % of total read count and nine mutations were not detected. We also detected GNAS 601 C>T using ultra-deep NGS (1.78 million X) in 0.77 % of amplicons reads. We were not able to detect mutation found in PA tissue in cfDNA using cast-PCR, indicating that the portion of mutation-containing ctDNA in total isolated cfDNA is too small to be detected with this method. Conclusions: For the first time, we demonstrate the possibility to detect somatic mutations of PA in cfDNA isolated from patients’ blood plasma. Whether the source of mutation detected in cfDNA is PA should be further tested.